Safety and Clinical Response in Ankylosing Spondylitis after Three Months of Etanercept Therapy - Roshaan Tahir; Nadeem Ashraf; Adnan Manzar; Muhammad Hamza Zaheer; Muhammad Asad Abbas; Ammarah Mehmood (Pakistan Armed Forces Medical Journal, 2024)
Abstract